2021
DOI: 10.1186/s13023-020-01642-y
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal hyperinsulinism in transient and classical forms of tyrosinemia

Abstract: Background The spectrum of disorders associated with hyperinsulinemic hypoglycemia (HHI) has vastly increased over the past 20 years with identification of molecular, metabolic and cellular pathways involved in the regulation of insulin secretion and its actions. Hereditary tyrosinemia (HT1) is a rare metabolic disorder associated with accumulation of toxic metabolites of the tyrosine pathway due to a genetically mediated enzyme defect of fumarylacetoacetate hydrolase. Transient tyrosinemia of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Affected children may occasionally present with CHI (156). Sethuram et al observed CHI also in one case of transient tyrosinemia of the newborn, which is a benign condition with a maturational defect of the enzymes associated with tyrosine metabolism without any genetic abnormalities (157). CHI in tyrosinemia type 1 is responsive to diazoxide and usually resolves within the first years of life (156,157).…”
Section: Soares Et Al Presented Another Case Of Chi and Polycystic Ki...mentioning
confidence: 99%
See 1 more Smart Citation
“…Affected children may occasionally present with CHI (156). Sethuram et al observed CHI also in one case of transient tyrosinemia of the newborn, which is a benign condition with a maturational defect of the enzymes associated with tyrosine metabolism without any genetic abnormalities (157). CHI in tyrosinemia type 1 is responsive to diazoxide and usually resolves within the first years of life (156,157).…”
Section: Soares Et Al Presented Another Case Of Chi and Polycystic Ki...mentioning
confidence: 99%
“…Sethuram et al observed CHI also in one case of transient tyrosinemia of the newborn, which is a benign condition with a maturational defect of the enzymes associated with tyrosine metabolism without any genetic abnormalities (157). CHI in tyrosinemia type 1 is responsive to diazoxide and usually resolves within the first years of life (156,157). Although islet-cell hypertrophy and hyperplasia have been reported in a number of cases of tyrosinemia type 1 (158), the precise pathophysiology of hyperinsulinism remains obscure.…”
Section: Soares Et Al Presented Another Case Of Chi and Polycystic Ki...mentioning
confidence: 99%